Evaluation of the CORE-10 to assess psychological distress in pregnancy. (26th May 2020) - Coates, Rose; Ayers, Susan; de Visser, Richard; Thornton, Alexandra
ABSTRACT: Background: Women experience diverse symptoms of mental ill-health in pregnancy, yet measures usually only assess depression or anxiety. Measures may, therefore, miss out on identifying women experiencing distress. Objective: We aimed to examine the validity and reliability of the CORE-10: a short measure with broad coverage of symptoms of distress and associated functioning, in pregnant women. Methods: 366 women 26–38 weeks pregnant completed online measures of distress (CORE-10), depression (Whooley questions), anxiety (Generalised Anxiety Disorder-2), and a single item measuring worry about psychological health. We examined convergent and factorial validity and concordance rates of the measures. Results: Levels of distress were high, with anxiety the most reported symptom. The CORE-10 showed good convergent validity. A two-factor structure representing 'symptoms' and 'ways of coping' best fit this sample. Internal reliability of the symptoms' factor was good. Discussion: The self-selected online sample may not be representative of pregnant women in the third trimester and a diagnostic interview was not used. Based on this validation study, the CORE-10 potentially offers an assessment of a broad range of symptoms of postnatal distress within the confines of a measure brief enough to be usable in clinical settings. Further validation is needed.